أساليب الري الحديثة ودورها في تحقيق التنمية الزراعية المستدامة تحليل الواقع الجزائري - بكاري نورالدين; كدودة عادل (جامعة الوادي University of Eloued, 2023)
هدف من خلال هذه الورقة البحثية إلى تسليط الضوء على إمكانية استخدام أساليب الري الحديثة ودورها في تحقيق التنمية الزراعية المستدامة في الزراعة الجزائرية وهذا من خلال تحليل الواقع الجزائري، حيث تطرقنا في البداية إلى ماهية التنمية الزراعية المستدامة وبعدها تناولنا أهم أساليب الري الحديث والمشاكل التي تعالجها هذه الأساليب وفي الأخير عالجنا علاقة الري الحديث بتحقيق التنمية الزراعية المستدامة بالجزائر مع الإشارة إلى التوصيات في آخر الدراسة، متبعين بذلك المنهج الوصفي والمنهج التحليلي في جل مراحل الدراسة. Through this research paper, our aim is to shed light on the possibility of using modern irrigation methods and their role in achieving sustainable agricultural development in Algerian agriculture, through an analysis of the Algerian situation. We begin by defining sustainable agricultural development, then we discuss the most important modern irrigation methods and the problems they address. Finally, we address the relationship between modern irrigation and achieving sustainable agricultural development in Algeria, with reference to recommendations in the conclusion of the study, following both the descriptive and analytical methods throughout the study
Modern irrigation methods and their role in achieving sustainable agricultural development. Analysis of the Algerian reality
Keywords: أساليب الري الحديثة; التنمية الزراعية المستدامة; الجزائر; Modern irrigation methods; Sustainable agricultural development; Algeria